PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN MELALUI APLIKASI QUIZIZZ DAN CANVA DI SDS SEMEN TONASA II KABUPATEN PANGKEP - Hamran, Hamran; Devila, Rego; Akib, Israwati; Agung, Eka Adnan; Hamriani, Hamriani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This service was carried out at SDS Semen Tonasa II Pangkep which is located in Pangkep Regency, South Sulawesi. The problem with partners is that teachers do not know and understand about the development of learning media based on the Quizizz and Canva applications. An alternative solution to the problem is providing training to teachers on developing learning media through the Quizizz and Canva applications at SDS Semen Tonasa II, Pangkep Regency. The output target to be achieved is that all SDS Semen Tonasa II Pangkep teachers know about the process of developing Quizizz and Canva learning media through material presentations. The method that will be carried out is the presentation of material about the importance of teachers having competence in developing learning media through the Quizizz and Canva application media as well as trials using learning media through the Quizizz and Canva applications at SDS Semen Tonasa II, Pangkep Regency. From the results of the activities that have been carried out, the results show that all teachers have carried out trials and already understand the development of learning media through the Quizizz and Canva applications.